Evaluation of primary caesarean section and neonatal outcomes in a tertiary care hospital and impact on current obstetric practice - Amey Chugh; Swati Lal; Tanvi Nijhawan; Pooja Biradar (Elsevier, 2023)
Objective: To evaluate the rising rates of primary caesarean section, its indications and neonatal outcomes. Study design: This was a prospective observational study of 1000 deliveries after 28 weeks gestation. The 312 primary caesarean section (CS) cases were studied with respect to their antepartum and postpartum outcomes. Results: The primary caesarean section (PCS) rate was 31.2% which had risen from 17% in 2018-2019 at the institute of study. The most common indication of PCS was found to be foetal distress (34.2%). Out of all PCS 25.64% were preterm deliveries. 57.05% of PCS born babies required NICU admission after birth and 59.93% had 1 min APGAR score < 7. The most common indication for NICU admission was respiratory distress (55.13%). Conclusion: The rising trend of CS can be attributed to rising PCS rate. Also the indications should be medically justified whenever a CS is attempted as it has significant adverse maternal as well as neonatal implications and also affects the subsequent pregnancy outcomes. CS delivered babies are more prone for respiratory distress syndrome (RDS) and NICU admissions.